Peripheral tactile sensory perception of older adults improved using subsensory electrical noise stimulation. Issue 8 (August 2016) - Breen, Paul P.; Serrador, Jorge M.; O'Tuathail, Claire; Quinlan, Leo R.; McIntosh, Caroline; ÓLaighin, Gearóid
Abstract: Loss of tactile sensory function is common with aging and can lead to numbness and difficulty with balance and gait. In previous work we found that subsensory electrical noise stimulation (SENS) applied to the tibial nerve improved tactile perception in the soles of the feet of healthy adults. In this work we aimed to determine if SENS remained effective in an older adult population with significant levels of sensory loss. Older adult subjects ( N = 8, female = 4, aged 65–80) had SENS applied via surface electrodes placed proximally to the medial and lateral malleoli. Vibration perception thresholds (VPTs) were assessed in six conditions, two control conditions (no SENS) and four SENS conditions (zero mean ± 15 µA, 30 µA, 45 µA and 60 µA SD). VPT was assessed at three sites on the plantar aspect of the foot. Vibration perception was significantly improved in the presence of ± 30 µA SENS and by 16.2 ± 2.4% (mean ± s.e.m.) when optimised for each subject. The improvement in perception was similar across all VPT test sites.